Vitamin D, obesity and bone health in children: the role of metabolic syndrome and MASLD - Hnida, Natalia Ihorivna; Гніда, Наталя Ігорівна; Гнiдой, Iгор Михайлович; Hnidoi, Ihor Mikhailovich (My University, 2025)
This article provides a narrative review of recent scientific literature regarding the complex interrelationship between vitamin D status, obesity, and bone health in the pediatric population. Vitamin D plays a pivotal role in calcium and phosphorus homeostasis, bone mineralization, and the regulation of bone turnover through osteoblast and osteoclast activity. A deficiency in this essential micronutrient during childhood can impair bone development and lead to conditions such as rickets, osteopenia, and osteoporosis. The high prevalence of vitamin D deficiency in children is associated with inadequate sun exposure, poor dietary intake, sedentary lifestyle, and underlying metabolic disturbances. A key focus of the review is the impact of obesity on vitamin D metabolism and skeletal health. Obesity not only reduces vitamin D bioavailability due to its sequestration in adipose tissue but also contributes to chronic low-grade inflammation and metabolic dysregulation, which adversely affect bone structure and function. Emerging evidence highlights that while higher body mass was once considered protective against bone fragility, recent studies suggest that excessive visceral fat, particularly in the presence of metabolic syndrome (MetS), may compromise bone quality and increase fracture risk. The article also explores the implications of metabolic dysfunction-associated steatotic liver disease (MASLD), which is increasingly diagnosed in overweight and obese children. MASLD may disrupt the newly recognized liver-bone axis, thereby contributing to altered bone remodeling and reduced bone mineral density. Furthermore, studies show that vitamin D deficiency is closely associated with the presence and severity of MASLD, suggesting a bidirectional relationship. The authors underscore the potential of vitamin D supplementation and lifestyle interventions, including improved nutrition and physical activity, as viable strategies to mitigate the adverse effects of obesity and MetS on pediatric skeletal health. The need for further clinical and translational research is emphasized to better understand the interactions among vitamin D status, adiposity, liver function, and bone development in children and adolescents. У статті представлено наративний огляд сучасної наукової літератури щодо складного взаємозв’язку між статусом вітаміну D, ожирінням і станом кісткової системи у дітей. Вітамін D відіграє ключову роль у підтриманні гомеостазу кальцію і фосфору, мінералізації кісток, а також регуляції процесів остеогенезу й резорбції кісткової тканини через вплив на остеобласти й остеокласти. Дефіцит цього важливого мікронутрієнта в дитячому віці може порушити нормальний розвиток скелету і спричинити рахіт, остеопенію та остеопороз. Висока поширеність дефіциту вітаміну D серед дітей пояснюється недостатнім впливом сонячного світла, незбалансованим харчуванням, малорухливим способом життя та метаболічними порушеннями. Окрему увагу приділено впливу ожиріння на обмін вітаміну D і здоров’я кісткової системи. Надлишкова маса тіла знижує біодоступність вітаміну D через його накопичення у жировій тканині, а також супроводжується хронічним низькоінтенсивним запаленням і метаболічною дезрегуляцією, які негативно впливають на структурута функцію кісткової тканини. Сучасні дослідження доводять, що попри раніше існуючу думку про «захисну роль» ожиріння для кісток, вісцеральне ожиріння, особливо в поєднанні з метаболічним синдромом, може знижувати якість кісткової тканини та підвищувати ризик переломів. Розглянуто також роль метаболічно асоційованої стеатозної хвороби печінки (MASLD), що дедалі частіше діагностується у дітей із надмірною вагою. MASLD спричиняє порушення функціонування так званої «печінково-кісткової осі», що додатково поглиблює дисбаланс у кістковому ремоделюванні. Доведено, що дефіцит вітаміну D корелює з наявністю і тяжкістю MASLD, що свідчить про взаємозалежність цих станів. Автори підкреслюють перспективність застосування вітаміну D та змін способу життя (раціонального харчування, фізичної активності) як ефективних підходів до профілактики порушень кісткової системи у дітей з ожирінням та метаболічними розладами. Наголошено на необхідності подальших досліджень для глибшого розуміння взаємодії між вітаміном D, жировою тканиною, функцією печінки та розвитком кісткової тканини в дитячому віці.
Hnida N. I. Vitamin D, obesity and bone health in children: the role of metabolic syndrome and MASLD / Hnida N. I., Hnidoi I. M. // Health & Education. - 2025. - Iss. 3. - P. 15-23. - Режим доступу: https://doi.org/10.32782/health-2025.3.2 ; https://hdl.handle.net/11300/31380 ; Опубліковано 17.10.2025 https://journals.medacad.rivne.ua/index.php/health-education/article/view/303
Keywords: vitamin D; obesity; children; bone tissue; osteoporosis; metabolic syndrome; MASLD; вітамін D; ожиріння; діти; кісткова тканина; остеопороз; метаболічний синдром